Floricanto Sí! : a collection of Latina poetry - Milligan, Bryce, 1953-; Milligan, Mary Guerrero; De Hoyos, Angela (New York : Penguin Books, 1998)
Throughout the United States, from the pens of new talents and major figures alike, a Latina poetic sensibility is emerging. The diverse ethnic heritages of the poets of [actual symbol not reproducible]Floricanto Si! inform and inspire a particularly American Latina culture. These pages shimmer with the sensual imagery and vibrancy of poetry that interprets America, identity, womanhood, love, and art in new ways.
Even the Eagles Must Gather -- Delicious Death -- Warrior in the Sand / Alma Luz Villanueva -- Contraries -- Glint.
"Penguin original"--Label on cover.
Keywords: American poetry -- Hispanic American authors; Hispanic American women -- Poetry; American poetry -- 20th century; Hispanic Americans -- Poetry